Sistem Budaya dalam Prosesi Pernikahan Adat Bima di Kecematan Donggo Kabupaten Bima (Kajian Antropolinguistik) - Imansyah, Ainul; Mahsun, Mahsun; Sirulhaq, Ahmad (Universitas Batanghari Jambi, 2025)
The purpose of this study was to describe the form of lingual units in the traditional wedding procession of Bima Kecematan Donggo Bima Regency, as well as to describe the cultural views of the people in the traditional wedding procession of Bima in Kecematan Donggo Bima Regency. Penelitin is a descriptive language research. The results showed that the form of lingual units in the traditional Bima wedding procession in Donggo District, Bima Regency, includes various words and phrases that are used specifically to mark each stage of the procession. Each of these lingual units has a deep meaning that corresponds to a cultural and symbolic value in each stage of the procession, from the beginning to the post-wedding. The people of Donggo Sub-District, Kabupaten Bima, still view traditional wedding processions as an important part of their cultural identity. This tradition is preserved for generations with the support of traditional leaders, youth, and humanists, who play an active role in maintaining and continuing this wedding custom as a form of togetherness and respect for ancestors.